2018
DOI: 10.13005/ojc/340648
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical Features of Symmetric and Asymmetric Supercapacitors Based on Nanostructured Mn-Cuo Electrodes

Abstract: Progress in material science has unearthed a number of options that offer great advantages for nanostructured electrode materials which enable supercapacitors to operate efficiently. Present work involves fabrication of symmetric and asymmetric type supercapacitor devices utilizing Mn-CuO nanostructures and activated carbon (AC) as electrode materials and subsequent investigation on their supercapacitive performance in 2M KOH aqueous electrolyte. The asymmetric supercapacitor device (Mn-CuO // 2M KOH// AC) dem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 8 publications
1
14
0
Order By: Relevance
“…[2,8] The literature review compared with present work is shown in Table 1. [2,9,[12][13][14][15][16][17][18] Furthermore, the specific capacitance performance for C 1 , MC 2 , MC 4 , and MC 6 electrodes is shown in Table 2.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…[2,8] The literature review compared with present work is shown in Table 1. [2,9,[12][13][14][15][16][17][18] Furthermore, the specific capacitance performance for C 1 , MC 2 , MC 4 , and MC 6 electrodes is shown in Table 2.…”
Section: Resultsmentioning
confidence: 99%
“…The FESEM of higher magnifications of MC 6 added in supporting information (S 1 ). From the literature survey, it is found that electrochemical properties of electrode material are highly dependent on surface morphology [2,13,23,32] …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is well‐known that, compared to the symmetric supercapacitors, the asymmetric supercapacitor devices have the advantage of higher energy and power density due to the non‐identical potential changes in the two dissimilar electrodes that provide longer discharge times and non‐identical discharge profiles resulting in higher energy and power performances 63 . However, a big issue lies in the charge balancing of the two electrodes 64 .…”
Section: Resultsmentioning
confidence: 99%
“…It is well-known that, compared to the symmetric supercapacitors, the asymmetric supercapacitor devices have the advantage of higher energy and power density due to the non-identical potential changes in the two dissimilar electrodes that provide longer discharge times and nonidentical discharge profiles resulting in higher energy and power performances. 63 However, a big issue lies in the charge balancing of the two electrodes. 64 Therefore, the supercapacitive performance of the active electrode (N-CNO) within a device, an N-CNO//N-CNO symmetric supercapacitive device is fabricated for better understanding, and corresponding device performance is compared with the asymmetric device presented above.…”
Section: Electrochemical Performance Of Symmetric N-cno//n-cno Superc...mentioning
confidence: 99%